Characteristic of Antioxidant-Rich “Teh Talua” Instant Using the Foam Mat Drying Method - Rasdiana, Felga Zulfia; Ismed, Ismed; Refdi, Cesar Welya; Fauzi, Yusma Resti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
This research aims to determine the formulation and characteristics of the best instant “teh talua” with the addition of red ginger and areca nut. In this study, 5 treatments were used, namely without addition (control), with the addition of red ginger juice (5% and 10%), and with the addition of areca nut extract (5% and 10%). The data obtained were subjected to statistical analysis using Analysis of Variant (ANOVA) and continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The results showed that each treatment had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, water activity (Aw), and antioxidant activity. The best treatment is treatment B (with the addition of red ginger juice 5%) with a water content of 17.90%, ash content of 1.58%, protein content of 3.09%, fat content of 12.39%, carbohydrate content of 64.98%, water activity (Aw) 0.523%, and antioxidant activity 54.98%.